Comparison of physiological responses and technical actions in full-court games in young basketball players - Köklü, Y.; Alemdaroglu, U.; Aksoy, I.; Gürmen, I. (Science & Sports, 2017)
Aim: The purpose of this study was to compare physiological responses and frequencies of technical actions in different full-court game formats in young basketball players. Methods: Twelve young male basketball players (age 15.8±0.9 years; height 184.1±7.7cm; body mass 77.2±10.8kg) participated in this study voluntarily. Different full-court game formats (2-a-side, 3-a-side, 4-a-side and 5-a-side) were organized in random order at 2-day intervals. Results: The study results indicate that the full-court 2-a-side and 3-a-side games produced significantly higher physiological responses than the full-court 5-a-side games in terms of HR, %HRmax, and RPE (P<0.05). In addition, the full-court 2-a-side games resulted in significantly higher frequencies of technical actions than full-court 4-a-side and 5-a-side games (P<0.05) with the exception of steals. Conclusion: The results of this study suggest that, if coaches want to achieve greater physiological responses and higher frequencies of technical actions, they should organize 2-a-side and 3-a-side full-court games.